Opportunities for developing digital career guidance In Hungary - Tibor Bors Borbély-Pecze; Katalin Gyöngyösi (Opuscula Theologica et Scientifica)
Digitalisation is a process that is transforming the framework of social and economic coexistence, and career development professionals must also be part of it. At the same time, the digital readiness and culture of individual European countries differ. The coronavirus crisis that started in 2020 has forced all of us to adapt to this digital challenge. In this article, we present the changes in Hungary and make recommendations for the possible directions of national development.